Annual Plan Proposals 1988-89 Government of Kerala - Planning Commission (Planning Commission, 1988)
The five year approved outlay of the State’s Seventh Plan is Rs. 2100 crores. During 1985-86, the State implemented a Plan of Rs. 408 crores and in 1986-87 Rs. 428 crores. For 1987-88 against an approved outlay of Rs. 440 crores, the State Government’s budget estimate is Rs. 472 crores. The likely expenditure may be even a little higher.
Government of Kerala